Restorative Justice Model through the Imposition of Compensation Punishment as the Main Punishment in Crimes Against Property - Chandra Firmasyah Yudhatama; Elza Qorina Pangestika (Rechtsnormen: Journal of Law, 2024)
Background. Efforts to resolve cases of crimes against property that have been carried out by imposing imprisonment have turned out to be unable to recover the losses suffered by victims. Purpose. Through restorative justice approach, the judge should be given the option to impose compensation to the victim as a main punishment which has not been regulated either in the Criminal Code or Criminal Code Bill. Method. The research method used is normative juridical with the approach of legislation, concept, and comparison. Results. The result of this research discussion provides an alternative solution or law enforcement of crimes against property by proposing the imposition of compensation to the victim as the main punishment that must be imposed by the judge as a new mechanism in the Indonesian legal system. Conclusion. This concept is different from the application of restorative justice that has been applied in Indonesia or abroad which applies it at the level of investigation and prosecution.